Tetraspanin CD82 interaction with cholesterol promotes extracellular vesicle–mediated release of ezrin to inhibit tumour cell movement - Chao Huang; Franklin A. Hays; James J. Tomasek; Siribhinya Benyajati; Xin A. Zhang (Journal of Extracellular Vesicles, 2020)
Tumour metastasis suppressor KAI1/CD82 inhibits tumour cell movement. As a transmembrane protein, tetraspanin CD82 bridges the interactions between membrane microdomains of lipid rafts and tetraspanin-enriched microdomains (TEMs). In this study, we found that CD82 and other tetraspanins contain cholesterol recognition/interaction amino-acid consensus (CRAC) sequences in their transmembrane domains and revealed that cholesterol binding of CD82 determines its interaction with lipid rafts but not with TEMs. Functionally, CD82 needs cholesterol binding to inhibit solitary migration, collective migration, invasion and infiltrative outgrowth of tumour cells. Importantly, CD82–cholesterol/–lipid raft interaction not only promotes extracellular release of lipid raft components such as cholesterol and gangliosides but also facilitates extracellular vesicle (EV)–mediated release of ezrin–radixin–moesin (ERM) protein Ezrin. Since ERM proteins link actin cytoskeleton to the plasma membrane, we show for the first time that cell movement can be regulated by EV-mediated releases, which disengage the plasma membrane from cytoskeleton and then impair cell movement. Our findings also conceptualize that interactions between membrane domains, in this case converge of lipid rafts and TEMs by CD82, can change cell movement. Moreover, CD82 coalescences with both lipid rafts and TEMs are essential for its inhibition of tumour cell movement and for its enhancement of EV release. Finally, our study underpins that tetraspanins as a superfamily of functionally versatile molecules are cholesterol-binding proteins. Abbreviations: Ab: antibody; CBM: cholesterol-binding motif; CCM: cholesterol consensus motif; CRAC/CARC: cholesterol recognition or interaction amino-acid consensus; CTxB: cholera toxin B subunit; ECM: extracellular matrix; ERM: ezrin, radixin and moesin; EV: extracellular vesicles; FBS: foetal bovine serum; mAb: monoclonal antibody; MST: microscale thermophoresis; pAb: polyclonal antibody; and TEM: tetraspanin-enriched microdomain